Analysis of Students' Critical Thinking Skills in Dynamic Electrical Material - Misbah Misbah; Saiyidah Mahtari; Mustika Wati; Muhdi Harto (Kasuari: Physics Education Journal (KPEJ), 2018)
Student learning achievement does not only depend on students' ability to solve problems. Learning achievement also depends on the suitability of the good questions, so the questions need to be tested for empirical validity. This study aims to analyze the problem of critical thinking skills. The research method is quantitative descriptive method. The subjects of the trial were 32 students of class XII IPA in high school in the city of Banjarmasin. The technique of collecting data uses a test of critical thinking skills. The results of the research data are processed using the RASCH model with the Winstep program to obtain information related to infit, outfit, and undimensionality items. The results showed that with the mean MNSQ OUTFIT criteria of 1.07, ZSTD OUTFIT 0, reliability based on item separation was 1.78 with special categories and proved to be fit tests with the model. The reliability of the question using apron cronbach is 0.64. Based on the RASCH analysis there are 3 questions that are outliert. The results of the study show that critical thinking skills in dynamic electrical material can be used with improvement.